Perencanaan sistem drainase berwawasan lingkungan di Kecamatan Liang Anggang, Kota Banjarbaru - Rony Riduan; Dewi Astuti Sri Devi Kurniawan (Regional Development Information Center, Universitas Sebelas Maret, 2026)
Several inundation points remain in Liang Anggang District due to insufficient drainage capacity to accommodate a five-year return period flood discharge. This condition highlights the need for environmentally oriented drainage planning to support sustainable regional development. This study aims to design an eco-drainage system through the application of infiltration wells to reduce surface runoff. Analyses included hydrological and hydraulic simulation using maximum daily rainfall data over a 10-year period (2013–2022). Runoff simulations before and after infiltration well implementation were conducted using the Storm Water Management Model (SWMM) with the Low Impact Development (LID) feature. The simulation results indicate that prior to implementation, 94 drainage channels experienced overflow. The application of 3,750 infiltration wells with a diameter of 1 m and a depth of 3 m significantly reduced the number of overflowing channels. Additionally, total runoff volume in Liang Anggang District decreased by 29%, from 585.03 × 10⁶ liters to 415.34 × 10⁶ liters. These findings demonstrate that environmentally oriented drainage systems are effective in mitigating urban flooding and supporting sustainable drainage infrastructure development.